The development of narrative identity in the psychodynamic treatment of avoidant personality disorder: A case study - Timberlake, Ashley Frances Volodina; Fesel, Daniel (Frontiers in Psychiatry, 2023)
Avoidant personality disorder (AvPD) is characterized by feelings of shyness, inadequacy, and restraint in intimate relationships and has been associated with a disturbance in narrative identity, which is the internalized and evolving story of past, present, and future experiences. Study findings have indicated that an improvement in overall mental health through psychotherapy may increase narrative identity. However, there is a lack of studies incorporating not only the examination of narrative identity development before and after psychotherapy but also within psychotherapy sessions. This case study examined the development of narrative identity in short-term psychodynamic psychotherapy treatment of a patient with AvPD, using therapy transcripts and life narrative interviews before, after, and 6 months following treatment termination. Narrative identity development was assessed in terms of agency, communion fulfillment, and coherence. Results showed that the patient’s agency and coherence increased over the course of therapy, whereas communion fulfillment decreased. At the six-month follow-up, agency and communion fulfillment increased, whereas coherence remained stable. The results of this case study suggest that the patient’s sense of narrative agency and ability to narrate coherently improved after undergoing short-term psychodynamic therapy. The decrease of communion fulfillment during psychotherapy and later increase after termination suggests that the patient became more aware of conflictual patterns in their relationships, therefore realizing that their wishes and desires were not being fulfilled in their current relationships. This case study displays the possible impact short-term psychodynamic therapy may have by helping patients with AvPD develop a narrative identity.